Mortality in Barrett’s esophagus: three decades of experience at a single center - Caygill, C. P. J.; Royston, C.; Charlett, A.; Wall, C. M.; Gatenby, P. A. C.; Ramus, J. R.; Watson, A.; Winslet, M.; Bardhan, K. D. (Endoscopy, 2012)
Background and study aims: There is a view that the majority of deaths in patients with Barrett’s esophagus are from causes other than esophageal adenocarcinoma (EAC). The aim of this analysis was to establish the pattern of mortality for a number of causes in patients with Barrett’s esophagus .Patients and methods: This was a single-center prospective cohort study of patients from Rotherham District General Hospital, which is a secondary referral center. The cohort consisted of 1239 patients who were diagnosed with Barrett’s esophagus between April 1978 and March 2009. Follow-up for mortality was undertaken by “flagging” the patients with the NHS Information Center. Causes of death were compared with UK Office of National Statistics age- and sex-specific mortality data for 1999, the median year of diagnosis. Analysis was by a “person – years at risk” calculation from date of diagnosis.Results: The ratio of observed deaths from EAC compared with those expected in this cohort was 25.02 – a very large excess. There was no difference in mortality from colorectal cancer or circulatory disease and there were fewer deaths from cancers other than esophageal adenocarcinoma and colon cancer compared with national statistics. There was a small statistically significant difference in mortality from all causes but this disappeared completely when deaths from esophageal adenocarcinoma were excluded.Conclusions: Overall, mortality in Barrett’s esophagus is increased significantly but only as a result of the large excess of deaths from EAC. This strengthens the case for endoscopic surveillance if successful interventions can be undertaken in patients with Barrett’s esophagus to prevent development of esophageal adenocarcinoma.